Roze & Blud : a poem - Iwen, Jayson, 1974- (Book collections on Project MUSE., 2020)
"In a book-length series of persona poems, Jayson Iwen examines the intimate thoughts and feelings of Americans whose lives have been predominantly ignored by contemporary mainstream culture. Through the eyes of a teenage girl growing up in a trailer park and a retired veteran sharing an apartment with an Afghan refugee, Iwen reveals the everyday heartbreak and beauty experienced by people living at the periphery of the nation's consciousness. Roze and Blud is gritty, gut-wrenching, gorgeous, and ultimately transcendent. It is a Spoon River Anthology for the 21st Century, a Waste Land for the heartland. Roze and Blud is a virtuoso performance, the kind of book that fundamentally transforms the way you see the world after you have experienced it... because you don't read it, you experience it. In addition to winning the Miller Williams Poetry Prize, Roze and Blud was a finalist for the National Poetry Series and the Green Rose Prize, as well as a semi-finalist for the Wheeler Prize and the Brittingham and Felix Pollak Prizes"--